Environmentally sustainable national income: Work in progress (Ökologisches Wirtschaften - Fachzeitschrift, 2012)
The calculation of the environmentally sustainable national income is not only relatively easy, it is also the best measure compared to other comparable alternative indices. The index deserves more attention because it is a useful scientific tool to provide society with essential information to decide upon future strategies of economic policy.